Understanding virtue ethics - Hooft, Stan van, 1945- (Understanding movements in modern thought., 2006)
After presenting a broad overview of the history of virtue ethics, this work explores virtues in the context of contemporary moral theory to analyse how many intractable moral dilemmas might be overcome by responsible, virtuous agents.